Self-reactivity of CD8 T-cell clones determines their differentiation status rather than their responsiveness in infections - Paprckova, Darina; Niederlova, Veronika; Moudra, Alena; Drobek, Ales; Pribikova, Michaela; Janusova, Sarka; Schober, Kilian; Neuwirth, Ales; Michalik, Juraj; Huranova, Martina; Horkova, Veronika; Cesnekova, Michaela; et al. (Frontiers in Immunology, 2022)
Mature T cells are selected for recognizing self-antigens with low to intermediate affinity in the thymus. Recently, the relative differences in self-reactivity among individual T-cell clones were appreciated as important factors regulating their fate and immune response, but the role of self-reactivity in T-cell biology is incompletely understood. We addressed the role of self-reactivity in T-cell diversity by generating an atlas of mouse peripheral CD8+ T cells, which revealed two unconventional populations of antigen-inexperienced T cells and examined the steady-state phenotype of monoclonal T cells with various levels of self-reactivity. Highly self-reactive clones preferentially differentiate into antigen-inexperienced memory-like cells, but do not form a population expressing type I interferon-induced genes, showing that these two subsets have unrelated origins. The functional comparison of naïve monoclonal CD8+ T-cells specific to the identical model antigen did not show any correlation between the level of self-reactivity and the magnitude of the immune response.